Swiss Ball Exercise on Core Muscles Fitness of Gym Enroll Peoples: Impact of Swiss Ball Exercise on Core Muscles Fitness of Gym Enroll Peoples (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this study was to examine the “Swiss ball exercise on core muscles fitness ofgym enroll peoples”. It was an experimental study in which pre-test post-test non equivalent groupsdesign was used. In this study gym enrolled and regularly exercise session attended 40 peoples mean ofage (32.17±4.10) were selected as sample by used simple random sampling technique from fitness gym,Shrigonda. Gym exercise peoples were selected into, male (n=25) and female (n=15). Sit-ups, trunkflexor, plank hold core muscles fitness and endurance test was conducted on both the groups obtaineddata was analyzed by using paired sample t-test. The results showed that statistics change of pre andpost tests performance of subjects on sit-ups, trunk flexor plank hold test for core muscles fitness wassignificant effect find out. It was also researcher concludes that there was significant improvement ofcore muscles fitness performance of male and female gym enroll peoples as compared to pre-test andpost-test performance due to the Swiss ball exercise given.